Surface-treated silica powder
By controlling the amount of physical adsorbed water per unit specific surface area of the surface-treated silica powder and the silane coupling agent treatment, the problem of insufficient fluidity of the dispersion is solved, more efficient dispersion and fluidity are achieved, and the performance of the resin composition is improved.
Patent Information
- Application Number
- CN202380089011.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-28
- Filing Date
- 2023-12-26
- Publication Date
- 2025-08-01
AI Technical Summary
In the prior art, the dispersion of surface-treated silica powder is insufficient in fluidity, making it difficult to meet the needs of efficient dispersion and flow.
By controlling the amount of physical adsorbed water (V/S) per unit specific surface area of the surface-treated silica powder within the range of 106≤V/S≤200, and the dispersion flowability of the powder is improved.
The dispersion fluidity of the surface-treated silica powder is significantly improved, the aggregation of fillers is reduced, the fluidity and fillability of the resin composition are enhanced, and a thinner sheet can be formed.
Smart Images

Figure BDA0005466800260000111
Abstract
Description
Technical Field
[0001] The present invention relates to a surface-treated silica powder. Background Art
[0002] To date, various developments have been made for surface-treated silica powders. As such a technique, for example, the technique described in Patent Document 1 is known.
[0003] Patent Document 1 describes a surface-treated silica particle material having a specific surface area of 10 to 150 m 2 / g (Claim 1 of Patent Document 1). The surface-treated silica particles in Test Example 1 of the Examples of this document were surface-treated with 3-methacryloxypropyltrimethoxysilane, and it was shown that their specific surface area was 43 m 2 / g and the carbon content was 0.9% by mass.
[0004] Prior Art Documents
[0005] Patent Documents
[0006] Patent Document 1: Japanese Unexamined Patent Application Publication No. 2020-111474 Summary of the Invention
[0007] However, as a result of investigations by the present inventors, it has been found that there is room for improvement in the fluidity of the dispersion containing the surface-treated silica particles described in Patent Document 1 above.
[0008] As a result of further investigations by the present inventors, it has been found that for a surface-treated silica powder, by appropriately controlling the amount of moisture after surface treatment, the fluidity of the dispersion containing the powder can be improved.
[0009] As a result of further in-depth research based on this finding, it has been found that by using the amount of moisture after surface treatment per unit specific surface area as an index and setting this index to a value equal to or higher than a specified value, the fluidity of the dispersion containing the surface-treated silica powder can be improved, and thus the present invention has been completed.
[0010] According to one aspect of the present invention, there is provided a surface-treated silica powder as follows.
[0011] 1. A surface-treated silica powder comprising silica particles surface-treated with a silane coupling agent, wherein,
[0012] Constitution: For the surface-treated silica powder, using the Karl Fischer method, measure the amount of water (ppm) generated until 200 °C, and set it as the amount V (ppm) of physically adsorbed water. Set the specific surface area of the surface-treated silica powder measured by the BET single-point method based on nitrogen adsorption as S (m 2 / g). When V and S satisfy 106 ≤ V / S ≤ 200.
[0013] 2. The surface-treated silica powder according to 1., wherein,
[0014] The specific surface area of the surface-treated silica powder measured by the BET single-point method based on nitrogen adsorption is 1.0 m 2 / g or more and 12.0 m 2 / g or less.
[0015] 3. The surface-treated silica powder according to 1. or 2., wherein,
[0016] The average sphericity is 0.80 or more.
[0017] 4. The surface-treated silica powder according to any one of 1. to 3., wherein,
[0018] The carbon content of the surface-treated silica powder obtained by the following step B is 0.09 mass% or more.
[0019] (Step B)
[0020] Add 3 g of the surface-treated silica powder to 37 g of acetone and stir for 30 minutes. Then, run the slurry in a centrifuge at 3500 rpm for 10 minutes to separate the surface-treated silica powder and acetone, and discard the supernatant of acetone. Perform this acetone-based cleaning operation twice and dry at 120 °C for 2 hours.
[0021] Measure the carbon content (mass%) in 0.3 g of the cleaned surface-treated silica powder by a carbon / sulfur simultaneous analyzer and perform quantification by the calibration curve method.
[0022] 5. The surface-treated silica powder according to any one of 1. to 3., wherein,
[0023] In the volume frequency particle size distribution of the surface-treated silica powder measured by the laser diffraction scattering method, when the particle size at which the cumulative value starting from the small particle size side becomes 50% is set as D50, D50 is 1 μm or more and 30 μm or less.
[0024] 6. The surface-treated silica powder according to any one of 1. to 4., wherein,
[0025] In the volume frequency particle size distribution of the surface-treated silica powder measured by the laser diffraction scattering method, when the particle diameters at which the cumulative values starting from the small particle size side are 10%, 50%, and 90% are defined as D10, D50, and D90, respectively, (D90 - D10) / D50 is 0.3 or more and 7.5 or less.
[0026] 7. The surface-treated silica powder according to any one of 1. to 5., wherein
[0027] the silane coupling agent contains a silane compound having one or more functional groups selected from the group consisting of an epoxy group, a methacrylic acid group, an acrylic acid group, an amino group, a vinyl group, an alkyl group, and a phenyl group.
[0028] 8. The surface-treated silica powder according to any one of 1. to 6., wherein
[0029] it is configured such that the thixotropy ratio of the evaluation sample measured under the following conditions is 0.021 or more.
[0030] (Condition)
[0031] Mix 50% by volume of the surface-treated silica powder and 50% by volume of a liquid silicone resin (DOWSIL SE1885A) to obtain an evaluation sample.
[0032] For the obtained evaluation sample, using a rheometer equipped with a conical tip (3 degrees), at 30 °C, when the viscosity measured at a shear rate of 1 [1 / s] is set as η1 and the viscosity measured at a shear rate of 100 [1 / s] is set as η 100 when, based on η 100 / η1, the above-mentioned thixotropy ratio is calculated.
[0033] According to the present invention, there is provided a surface-treated silica powder having excellent fluidity of the dispersion. Detailed Description
[0034] The outline of the surface-treated silica powder of the present embodiment will be described.
[0035] The surface-treated silica powder of the present embodiment contains silica powder surface-treated with a silane coupling agent, and is configured such that for the surface-treated silica powder measured by the Karl Fischer method, using the Karl Fischer method, the amount of water generated (ppm) until reaching 200 °C is measured and set as the amount of physically adsorbed water V (ppm), and when the specific surface area of the surface-treated silica powder measured by the BET single-point method based on nitrogen adsorption is set as S (m 2 / g), V and S satisfy 106 ≤ V / S ≤ 200.
[0036] According to the insight of the present inventors, it has been found that for surface-treated silica powder, by using the physically adsorbed water amount per unit area after surface treatment (V / S) as an index, it is possible to appropriately evaluate the stable state of surface modification using a silane coupling agent. As a result of further investigation, it has been found that by setting the aforementioned index (V / S) to be equal to or higher than the above lower limit value, the fluidity of a dispersion containing the surface-treated silica powder can be improved.
[0037] The lower limit of V / S of the surface-treated silica powder is 106 or more, preferably 107 or more. Thereby, the fluidity of the dispersion can be improved.
[0038] The upper limit of V / S of the surface-treated silica powder is 200 or less, preferably 190 or less, more preferably 180 or less. Thereby, the aggregation of the filler can be improved.
[0039] The lower limit of the specific surface area (S) of the surface-treated silica powder measured by the BET single-point method based on nitrogen adsorption is, for example, 1.0 m 2 / g or more, preferably 2.5 m 2 / g or more, more preferably 2.9 m 2 / g or more. Thereby, the addition amount to the resin can be increased, and the thermal expansion rate of the resin composition can be suppressed.
[0040] The upper limit of the specific surface area (S) of the above surface-treated silica powder is, for example, 12.0 m 2 / g or less, preferably 8.5 m 2 / g or less, more preferably 7.0 m 2 / g or less. Thereby, the aggregation of the filler can be suppressed.
[0041] For the BET single-point method based on nitrogen adsorption, a specific surface area measuring device (for example, manufactured by Yuasa Ionics Co., Ltd., device name: MONOSORB) can be used, and nitrogen is used as the adsorption gas and helium is used as the carrier gas. After drying and degassing 1 g of the sample under the conditions of 300 °C for 15 minutes, the measurement is carried out.
[0042] In the volume frequency particle size distribution of the surface-treated silica powder measured by the laser diffraction scattering method, the particle size at which the cumulative value starting from the small particle size side becomes 10% is defined as D10, the particle size at which the cumulative value becomes 50% is defined as D50, and the particle size at which the cumulative value becomes 90% is defined as D90.
[0043] The lower limit of D50 is, for example, 1 μm or more, preferably 4 μm or more, more preferably 8 μm or more. Thereby, the filling property to the resin can be improved.
[0044] The upper limit of D50 is, for example, 30 μm or less, preferably 20 μm or less, more preferably 15 μm or less. Thereby, the amount of coarse particles can be reduced, and the sheet thickness can be made thinner when the resin composition is formed into a sheet.
[0045] The lower limit of (D90 - D10) / D50 is, for example, 0.3 or more, preferably 0.7 or more, more preferably 1.0 or more. Thereby, the amount of coarse particles can be reduced, and the sheet thickness can be made thinner when the resin composition is formed into a sheet.
[0046] The upper limit of (D90 - D10) / D50 is, for example, 7.5 or less, preferably 7.0 or less, more preferably 6.5 or less. Thereby, the fluidity of the resin composition can be further improved.
[0047] The lower limit of the average sphericity of the surface-treated silica powder is, for example, 0.80 or more, preferably 0.85 or more, more preferably 0.90 or more. Thereby, the fluidity of the resin composition can be further improved.
[0048] In addition, the upper limit of the average sphericity of the surface-treated silica powder is not particularly limited and can be, for example, 0.99 or less.
[0049] Regarding the carbon content (C) of the surface-treated silica powder, it is determined according to the following step B.
[0050] (Step B)
[0051] Add 3 g of the surface-treated silica powder to 37 g of acetone and stir for 30 minutes. Then, run the slurry in a centrifuge at 3500 rpm for 10 minutes to separate the surface-treated silica powder and acetone, and discard the supernatant of acetone. Perform this acetone-based cleaning operation twice and dry at 120 °C for 2 hours.
[0052] Measure the carbon content (mass%) in 0.3 g of the washed surface-treated silica powder by a carbon / sulfur simultaneous analyzer and perform quantification by the calibration curve method.
[0053] The upper limit of the carbon content (C) of the surface-treated silica powder is, for example, 0.4 mass% or less, preferably 0.3 mass% or less, more preferably 0.2 mass% or less.
[0054] On the other hand, the lower limit of the carbon content (C) of the surface-treated silica powder is, for example, 0.09 mass% or more, preferably 0.10 mass% or more, more preferably 0.11 mass% or more.
[0055] The surface-treated silica powder can be configured such that the thixotropy ratio of the evaluation sample measured under the following conditions is 0.021 or more.
[0056] The lower limit of the thixotropy ratio described above is, for example, 0.021 or more, preferably 0.030 or more, and more preferably 0.040 or more. Thereby, sedimentation of the filler in the resin can be reduced.
[0057] The upper limit of the thixotropy ratio described above is, for example, 0.50 or less, preferably 0.40 or less, and more preferably 0.30 or less. Thereby, the fluidity of the resin composition can be further improved.
[0058] (Measurement conditions for the thixotropy ratio of the evaluation sample)
[0059] Mix 50 vol% of surface-treated silica powder and 50 vol% of liquid silicone resin (DOWSIL SE1885A) to obtain the above evaluation sample.
[0060] For the obtained evaluation sample, using a rheometer (manufactured by Anton Paar GmbH, model Modular Compact Rheometer MCR 102) equipped with a conical cone head (3 degrees), at 30 °C, the viscosity when measured at a shear rate of 1 [1 / s] is set as η1, and the viscosity when measured at a shear rate of 100 [1 / s] is set as η 100 When, according to η 100 / η1, the above thixotropy ratio is calculated.
[0061] In the present embodiment, for example, by appropriately selecting the preparation method of the raw material silica powder, the surface treatment method of the raw material silica powder, etc., the above hydrophobicity degree and carbon content can be controlled. Among these, as factors for setting the above hydrophobicity degree and carbon content within a desired numerical range, for example, the following can be cited: appropriately adjusting the specific surface area of the raw material silica powder; depending on the type of silane coupling agent, performing water retention treatment on the raw material silica powder so that the moisture content of physically adsorbed water per unit specific surface area becomes relatively large; maintaining the state in which the raw material silica powder subjected to water retention treatment is mixed with the silane coupling agent for a specified period, etc.
[0062] The silica powder only needs to contain silica (SiO2) as the main component.
[0063] The main component means that, in the total amount of the silica powder, in terms of mass conversion, for example, it contains 50% or more of silica (SiO2), preferably 80% or more, and more preferably 90% or more.
[0064] The silica powder contains either or both of amorphous and crystalline forms.
[0065] Regarding the silica powder, the amorphous ratio measured by the following method is preferably 95% or more, more preferably 97% or more. Regarding the amorphous ratio, using a powder X-ray diffractometer (for example, the product name "Model MiniFlex" manufactured by Rigaku Corporation, Japan), X-ray diffraction analysis is performed in the range of 2θ of CuKα ray from 26° to 27.5°, and the measurement is carried out based on the intensity ratio of specific diffraction peaks. In the case of silica powder, crystalline silica has a main peak at 26.7°, but there is no peak in amorphous silica. If amorphous silica and crystalline silica coexist, a peak height of 26.7° corresponding to the ratio of crystalline silica can be obtained. Therefore, based on the ratio of the X-ray intensity of the sample to the X-ray intensity of the crystalline silica standard sample, the coexistence ratio of crystalline silica (X-ray diffraction intensity of the sample / X-ray diffraction intensity of crystalline silica) is calculated, and the amorphous ratio (%) = (1 - coexistence ratio of crystalline silica) × 100 is obtained according to the formula.
[0066] Regarding the silane coupling agent, for example, a silane coupling agent containing a silane compound having one or more functional groups selected from the group consisting of an epoxy group, a methacrylic acid group, an acrylic acid group, an amino group, a vinyl group, an alkyl group, a phenyl group, a mercapto group, a styryl group, an acid anhydride group, a ureido group, an isocyanurate group, and an isocyanate group can be used. Preferably, a silane coupling agent containing a silane compound having one or more functional groups selected from the group consisting of an epoxy group, a methacrylic acid group, an acrylic acid group, an amino group, a vinyl group, an alkyl group, and a phenyl group can be used.
[0067] The above-mentioned silane compound has one or more hydrolyzable groups in the molecule in addition to the functional group.
[0068] As the hydrolyzable group, for example, alkoxy groups such as methoxy group and ethoxy group can be used.
[0069] The alkoxy group generates a silanol group by hydrolysis. This silanol group chemically reacts with the OH group (reaction point) present on the surface of the silica particles, enabling the silane coupling agent to be chemically bonded to the surface of the silica particles.
[0070] In addition, the surface-treated silica powder has a silane coupling agent chemically bonded and / or physically bonded to the surface of the silica particles.
[0071] Examples of the silane compound having an epoxy group include 3-glycidoxypropyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltriethoxysilane, etc.
[0072] Examples of the silane compound having a methacrylic group include 3-methacryloxypropyltrimethoxysilane, 8-methacryloxyoctyltrimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, and the like.
[0073] Examples of the silane compound having an acrylic group include 3-acryloxypropyltrimethoxysilane and the like.
[0074] Examples of the silane compound having an amino group include N-phenyl-3-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, hydrochloride of N-(vinylbenzyl)-2-aminoethyl-3-aminopropyltrimethoxysilane, and the like.
[0075] Examples of the silane compound having a vinyl group include vinyltrimethoxysilane, 7-octenyltrimethoxysilane, vinyltriethoxysilane, and the like.
[0076] Examples of the silane compound having an alkyl group include hexyltrimethoxysilane, octyltriethoxysilane, decyltrimethoxysilane, and the like.
[0077] Examples of the silane compound having a phenyl group include phenyltrimethoxysilane, trimethoxy(2-phenylethyl)silane, and the like.
[0078] Next, a method for manufacturing the surface-treated silica powder will be described.
[0079] An example of the method for manufacturing the surface-treated silica powder includes the following steps: a surface treatment in which a silane coupling agent is made to react with the surface of silica particles by bringing the silane coupling agent into contact with the silica powder, thereby obtaining the surface-treated silica powder.
[0080] Regarding the silica powder as the raw material, silica powder manufactured by any method can be used. For example: silica powder obtained by putting the powder obtained by crushing silica stone, silica sand, quartz, etc. into a flame or high-temperature plasma and spheroidizing it; silica powder obtained by synthesizing and spheroidizing through gas-phase hydrolysis of silicon tetrachloride and silica powder obtained by using it as the raw material and performing calcination, flame spraying treatment and spheroidizing it; silica powder obtained by synthesizing and spheroidizing metal silicon and alkoxysilane as starting materials in the gas phase or liquid phase and further performing calcination, flame spraying treatment and spheroidizing it, etc.
[0081] As a method of surface treatment using a silane coupling agent, known techniques such as dry method and wet method can be adopted, but the dry method is preferably adopted.
[0082] As the dry method, as long as it is a method of bringing the silane coupling agent into contact with the spherical silica powder (raw material) in a solid state, there is no particular limitation, and a known method can be adopted. For example, a stirring method with shear force, a mixing method using a ball mill, a mixer, etc. can be cited. Here, the solid state means a state in which the raw material silica powder is not dispersed in the dispersion medium.
[0083] In addition, when treating with a silane coupling agent, an acidic substance or a basic substance can coexist.
[0084] Moreover, as an example of the manufacturing method of surface-treated silica powder, the silane coupling agent can be brought into contact with the silica powder, and the OH group density derived from physically adsorbed water of the silica powder calculated according to the following steps is, for example, 7.0 per nm 2 Preferably 8.0 per nm or more 2 More preferably 9.0 per nm or more 2 or more.
[0085] (Step)
[0086] For the silica powder (raw material) before surface treatment, using the Karl Fischer method, measure the amount of water (ppm) generated until it reaches 200 °C, and set it as the amount of physically adsorbed water.
[0087] Calculate the number of OH groups based on the amount of physically adsorbed water obtained, and divide it by the specific surface area of the silica powder measured by the BET single-point method based on nitrogen adsorption, thereby calculating the OH group density derived from physically adsorbed water (per nm 2 ).
[0088] As an example of a method for manufacturing surface-treated silica powder, a water retention treatment in which water is brought into contact with silica powder (raw material) can be carried out before bringing a silane coupling agent into contact.
[0089] The lower limit of the addition amount of water here is, for example, 0.1% by mass or more, preferably 0.25% by mass or more, and more preferably 0.5% by mass or more with respect to 100% by mass of the silica powder. Thereby, the OH group density derived from physically adsorbed water in the silica powder can be increased.
[0090] The upper limit of the addition amount of water is, for example, 3.0% by mass or less, preferably 2.0% by mass or less, and more preferably 1.5% by mass or less with respect to 100% by mass of the silica powder. Thereby, aggregation of the raw material silica powder can be suppressed.
[0091] Next, the dispersion of the present embodiment will be described.
[0092] The dispersion of the present embodiment contains the above-described surface-treated silica powder and a solvent.
[0093] Examples of the solvent include water, organic solvents, resins, etc. By using water and / or an organic solvent as the solvent, a slurry can be formed, and by using a resin, a resin composition can be formed.
[0094] A composition obtained by incorporating the surface-treated silica powder of the present invention into a resin composition can be suitably used as a resin molding material (dispersion).
[0095] The resin composition contains a resin, known resin additives, etc. in addition to the surface-treated silica powder of the present invention.
[0096] In the resin composition, the surface-treated silica powder can be used alone or in combination with other fillers. In the resin composition, 10 to 99% by mass of the surface-treated silica powder can be contained, or 10 to 99% by mass of a mixed inorganic powder containing the surface-treated silica powder and other fillers can be contained. And in the mixed inorganic powder, the content of other fillers can be, for example, 1 to 20% by mass, 3 to 15% by mass with respect to 100% by mass of the surface-treated silica powder.
[0097] In addition, in this specification, unless otherwise specified, "~" means including the upper limit value and the lower limit value.
[0098] Examples of the above-described other fillers include untreated silica (crystalline silica, fused silica, etc.), alumina, titanium dioxide, silicon nitride, aluminum nitride, silicon carbide, talc, calcium carbonate, etc. particles other than the above-described surface-treated silica powder.
[0099] Regarding the average particle diameter of other fillers, for example, fillers of about 2 to 100 μm are used, and there are no particular restrictions on their particle size composition and shape.
[0100] Examples of the above resins include polyamides such as epoxy resins, silicone resins, phenolic resins, melamine resins, urea resins, unsaturated polyesters, fluororesins, polyimides, polyamide-imides, polyether-imides, polybutylene terephthalate, polyethylene terephthalate and other polyesters, polyphenylene sulfide, wholly aromatic polyesters, polysulfone, liquid crystal polymers, polyethersulfone, polycarbonate, maleimide-modified resins, ABS resins, AAS (acrylonitrile-acrylate rubber-styrene) resins, AES (acrylonitrile-ethylene-propylene-diene rubber-styrene) resins, acrylic resins, etc. These can be used alone or in combination of two or more.
[0101] The embodiments of the present invention have been described above, but these are examples of the present invention, and various structures other than the above can also be adopted. Moreover, the present invention is not limited to the above embodiments, and modifications, improvements, etc. within the scope of achieving the object of the present invention are included in the present invention.
[0102] Examples
[0103] Hereinafter, the present invention will be described in detail with reference to examples, but the present invention is not limited by any of the descriptions of these examples.
[0104] <Manufacture of surface-treated silica powder>
[0105] (Examples 1 to 7)
[0106] Silica powder having a specific surface area shown in Table 1 was prepared. The prepared silica powder was stored in a container at a temperature of 30 °C and a humidity of 80% for 72 hours (water retention treatment).
[0107] Next, in an environment of atmospheric pressure, a temperature of 25 °C, and a humidity of 65%, while adding a silane coupling agent (manufactured by Shin-Etsu Chemical Co., Ltd., a silane coupling agent containing a methacrylic acid group, KBM-503) to the silica powder after the water retention treatment, they were mixed and then left standing for 30 days under the same environmental conditions (surface treatment), and the surface-treated silica powder 30 days after adding the coupling agent was recovered.
[0108] (Comparative Examples 1 to 4)
[0109] For the prepared silica powder having the specific surface area shown in Table 1, without performing the above moisture retention treatment, after performing a drying treatment using a dryer between 150 and 200 °C (wherein, in Comparative Examples 1 to 3, the drying treatment time was adjusted respectively), surface treatment was performed in the same manner as in Example 1, and the surface-treated silica powder 30 days after adding the coupling agent was recovered.
[0110] (Examples 8 to 12)
[0111] For the silica powder after drying treatment and before surface treatment obtained in Comparative Example 3, relative to 100% by mass of the silica powder shown in Table 1, water in the addition amount shown in Table 1 was added, and after mixing them (moisture retention treatment), surface treatment was performed in the same manner as in Example 1, and the surface-treated silica powder 30 days after adding the coupling agent was recovered.
[0112] (Example 13)
[0113] The silane coupling agent was changed to a silane coupling agent containing an alkyl group (KBM-3083), and except for this, the surface-treated silica powder 30 days after adding the coupling agent was recovered in the same manner as in Example 8.
[0114] (Example 14)
[0115] The silane coupling agent was changed to a silane coupling agent containing a phenylamino group (KBM-573), and except for this, the surface-treated silica powder 30 days after adding the coupling agent was recovered in the same manner as in Example 8.
[0116] [Table 1]
[0117]
[0118] The silica powder before surface treatment (raw material) or the surface-treated silica powder 30 days after adding the coupling agent was used as a sample, and the following items were evaluated.
[0119] <Specific surface area>
[0120] The specific surface area of the powder was measured by the BET single-point method based on nitrogen adsorption.
[0121] Specifically, using a specific surface area measuring device (manufactured by Yuasa Ionics Co., Ltd., device name: MONOSORB), and using nitrogen as the adsorption gas and helium as the carrier gas, after drying and degassing 1 g of the sample under the conditions of 300 °C and 15 minutes, the measurement was performed.
[0122] In addition, it was confirmed that the specific surface area of the surface-treated silica powder in each example became the same value as that of the silica powder used as the raw material.
[0123] <Particle Size>
[0124] Using a particle size distribution measuring device (manufactured by MicrotracBEL Corporation, MT-3300EXII), the volume frequency particle size distribution of the powder was determined by the wet laser diffraction scattering method. Water was used as the solvent. As a pretreatment, homogenization treatment was performed at an output of 200 W for 1 minute to disperse the powder in the solvent, and the resulting dispersion was used as the measurement object. Then, based on the obtained volume frequency particle size distribution, the particle size (DX) at which the cumulative value starting from the small particle size side became X% was calculated.
[0125] <Average Sphericity>
[0126] Regarding the average sphericity of the powder, the particle images obtained by photographing with a stereomicroscope (e.g., model "SMZ-10" manufactured by Nikon Corporation), a scanning electron microscope, etc. were read into an image analysis device (e.g., manufactured by Nippon Avionics Co., Ltd., etc.), and the measurement was performed as follows. That is, the projected area (A) and the perimeter (PM) of the particles were measured from the photograph. If the area of the perfect circle corresponding to the perimeter (PM) is set as (B), the circularity of the particle can be expressed as A / B. Therefore, assuming a perfect circle with the same perimeter (PM) as the sample particle, PM = 2πr and B = πr 2 , so B = π×(PM / 2π) 2 , and the sphericity of each particle can be calculated as sphericity = A / B = A×4π / (PM) 2 . The circularities of any 200 particles thus obtained were determined and their average value was taken as the average sphericity.
[0127] The average sphericity of the silica powder of Example 1 was 0.90.
[0128] In addition, it was confirmed that the average sphericity of the surface-treated silica powder in each example became almost the same value as that of the silica powder used as the raw material.
[0129] <Moisture Content>
[0130] The moisture content in the silica powder or the surface-treated silica powder was measured by the Karl Fischer method.
[0131] Specifically, using a trace moisture measurement device (manufactured by Mitsubishi Chemical Corporation, model CA-05), the powder was placed in a quartz tube in the moisture vaporization mechanism, heated from room temperature to 900 °C with an electric heater while supplying dehydrated argon as the carrier gas, and the water vapor volatilized from the powder surface was introduced into the moisture measurement mechanism to measure the moisture content.
[0132] The moisture generated until the heating temperature of the electric heater reached 200 °C was regarded as physically adsorbed water, the moisture generated above 200 °C and up to 550 °C was regarded as water originating from hydrogen-bonded OH groups, and the moisture generated above 550 °C and up to 900 °C was regarded as water generated by dehydration condensation of isolated OH groups.
[0133] <OH group density>
[0134] Regarding the OH group density, it was calculated according to the following formula.
[0135] OH group density (number / nm 2 ) = 0.0668 × P / Q
[0136] In addition, in the above formula, P (ppm) was set as the moisture content of the powder measured by the Karl Fischer method in the above <moisture content>, and Q (m 2 / g) was set as the specific surface area of the powder measured by the BET single-point method based on nitrogen adsorption in the above <specific surface area>.
[0137] The value of the OH group density originating from physically adsorbed water was recorded in Table 1.
[0138] <Carbon content>
[0139] 3 g of surface-treated silica powder was added to 37 g of acetone and stirred for 30 minutes to obtain a slurry. Then, the slurry was centrifuged at 3500 rpm for 10 minutes to separate the surface-treated silica powder and acetone, and the supernatant of acetone was discarded. This acetone-based cleaning operation was performed twice, and it was dried at 120 °C for 2 hours.
[0140] The carbon content (mass%) in 0.3 g of the surface-treated silica powder after cleaning was measured by a carbon / sulfur simultaneous analyzer “CS-444LS type” (manufactured by LECO Corporation), and quantification was performed by the calibration curve method.
[0141] <Viscosity>
[0142] A 50 vol% mixture of surface-treated silica powder and 50 vol% of a liquid silicone resin (DOWSIL SE1885A) was obtained as an evaluation sample.
[0143] For the obtained evaluation samples, using a rheometer with a conical cone head (3 degrees) (manufactured by Anton Paar GmbH, model Modular Compact Rheometer MCR 102), the viscosity (η1) at a shear rate of 1 [1 / s] and the viscosity (η 100 ) were measured at 30°C. And, the thixotropy ratio was calculated from η 100 / η1.
[0144] Good: Since the viscosity in the low-shear region is low, it is judged that the fluidity of the dispersion is good.
[0145] Poor: Since the viscosity in the low-shear region is high or solidified, it is judged that the fluidity of the dispersion is poor.
[0146] Compared with Comparative Examples 1 to 4, the surface-treated silica powders of Examples 1 to 14 showed excellent results in the fluidity in the dispersion.
[0147] This application claims priority based on Japanese Patent Application No. 2022-212399 filed on December 28, 2022, and incorporates the entire contents disclosed therein into this case.
Claims
1. A surface-treated silica powder, which comprises silica particles surface-treated with a silane coupling agent, wherein, Constitution: For the surface-treated silica powder, using the Karl Fischer method, measure the amount of water (ppm) generated until reaching 200 °C, set it as the amount V (ppm) of physically adsorbed water, and set the specific surface area of the surface-treated silica powder measured by the BET single-point method based on nitrogen adsorption as S (m 2 / g). When V and S satisfy 106 ≤ V / S ≤ 200.
2. The surface-treated silica powder according to claim 1, wherein, The specific surface area of the surface-treated silica powder measured by the BET single-point method based on nitrogen adsorption is 1.0 m 2 / g or more and 12.0 m 2 / g or less.
3. The surface-treated silica powder according to claim 1 or 2, wherein, The average sphericity is 0.80 or more.
4. The surface-treated silica powder according to claim 1 or 2, wherein, The carbon content of the surface-treated silica powder determined by the following step B is 0.09% by mass or more, Step B: Add 3 g of the surface-treated silica powder to 37 g of acetone and stir for 30 minutes. Then, run the slurry in a centrifuge at 3500 rpm for 10 minutes to separate the surface-treated silica powder and acetone, discard the supernatant of acetone, perform this acetone-based cleaning operation twice, and dry at 120 °C for 2 hours. Measure the carbon content (% by mass) of 0.3 g of the cleaned surface-treated silica powder by a carbon / sulfur simultaneous analyzer and perform quantification by the calibration curve method.
5. The surface-treated silica powder according to claim 1 or 2, wherein, In the volume frequency particle size distribution of the surface-treated silica powder measured by the laser diffraction scattering method, when the particle size at which the cumulative value starting from the small particle size side becomes 50% is defined as D50, D50 is 1 μm or more and 30 μm or less.
6. The surface-treated silica powder according to claim 1 or 2, wherein, In the volume frequency particle size distribution of the surface-treated silica powder measured by the laser diffraction scattering method, when the particle sizes at which the cumulative values starting from the small particle size side become 10%, 50%, and 90% are defined as D10, D50, and D90 respectively, (D90 - D10) / D50 is 0.3 or more and 7.5 or less.
7. The surface-treated silica powder according to claim 1 or 2, wherein, The silane coupling agent contains a silane compound having one or more functional groups selected from the group consisting of an epoxy group, a methacrylic acid group, an acrylic acid group, an amino group, a vinyl group, an alkyl group, and a phenyl group.
8. The surface-treated silica powder according to claim 1 or 2, wherein, It is configured that the thixotropy ratio of the evaluation sample measured under the following conditions is 0.021 or more, Conditions: Mix 50% by volume of the surface-treated silica powder and 50% by volume of the liquid silicone resin DOWSIL SE1885A to obtain an evaluation sample. For the obtained evaluation sample, a rheometer with a conical cone head having a cone angle of 3 degrees is used. At 30 °C, the viscosity when measured at a shear rate of 1 [1 / s] is set as η1, and the viscosity when measured at a shear rate of 100 [1 / s] is set as η 100 When, according to η 100 / η1, the thixotropy ratio is calculated.
Citation Information
Patent Citations
Silica particle material, and silica particle material dispersion
JP2020111474A